Peran Mission for Migrant Workers (MFMW) dalam Advokasi Perlindungan Hak-Hak Buruh Migran Filipina di Hong Kong - Agung Setiyo Wibowo (Andalas Journal of International Studies (AJIS), 2015)
Migration has attracted international concern for decades. It challenges receiveing countries due to pressure to balance the need of domestic business and labor market,as well as the obligation to promote and protect the rights of migrant workers. The sending countries have also interest to balance the need of migrants and receiving countries. This research analyzes the role of Mission for Migrant Workers (MFMW)’s advocacy to protect the rights of Filipino migrants in Hong Kong. This paper concluded that the success of advocacy is strongly influenced by both domestic and transnational coalition.Keywords: Filipino migrant, Mision for Migrant Workers, transnationala advocacy network, Hong Kong